MU’TAZILA IN WESTERN SCHOLARSHIP: THEIR ORIGIN, ORIGINALITY, AND LEGACY - Ayub (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
Abstract Mu'tazila is one of the schools of kalam that appears in Islamic intellectual history. Although considered a heresy, the Mu'tazilite scholars played an important role in the development of various traditional Islamic disciplines. Initially, Western historians considered Mu'tazila rationalism as an anomaly in Islamic history. However, various studies show that they are not only an integral part of the Islamic intellectual tradition, but they have also even influenced Islamic scholars from various Islamic schools of thought in the next generation. This article will focus on the narrative of the Mu'tazila in Western scholarship by focusing on the history of its early emergence and development, the originality of the theological and philosophical ideas they developed, and their intellectual legacy in Islamic intellectual history. This research is library research with content analysis approach. This article shows that despite their adoption of foreign concepts and methods, especially from Greek philosophers, Mu'tazilite thinkers had developed their own original ideas. Furthermore, this paper will also discuss Mu'tazila's influence on scholars who came after them, not only in Islamic theology, but also in other fields of Islamic sciences.